The Anti-inflammatory Activity of Essential Oil from the Peel of Kaffir Lime (Citrus hystrix DC.) In vitro - Yanti Yemima, Yanti Yemima (Talenta Publisher, 2025)
Inflammation is a defense response of the body to injury or infection caused by foreign substances entering the body. This study aims to evaluate the toxicity and inhibition of nitric oxide (NO) production in RAW 264.7 cells. The essential oil from the peel of Kaffir lime (Citrus hystrix DC.) was isolated using microwave-assisted extraction. The essential oil was tested in vitro for cell viability in RAW 264.7 cells using the MTT assay and for the inhibition of NO production using the Griess assay, which was induced by LPS. The results showed that the viability of RAW 264.7 cells treated with the essential oil from Kaffir lime peel at concentrations of 1.56 and 0.78 µg/mL exhibited a cell viability percentage of >90% (90.29 ± 5.19; 92.71 ± 3.28). The NO production inhibition assay showed that the essential oil at concentrations of 1.56 and 0.87 µg/mL reduced NO levels in RAW 264.7 cells induced by LPS (9.58 ± 0.38; 10.16 ± 0.49). These concentrations of essential oil (1.56 and 0.78 µg/mL) were significantly different from the lipopolysaccharide control. Therefore, the essential oil from Kaffir lime peel demonstrates anti-inflammatory activity.